K.H.MUHAMMAD SALEH THAHA Semangat Belajar, Kemandirian, dan Kepedulian - Muhammad Hamdar Arraiyyah (Balai Penelitian dan Pengembangan Agama Makassar, 2019)
This paper is intended to describe a short biography of a Muslim scholar (ulama) named K.H. Muhammad Saleh Thaha (d. 1999). Description focuses on some aspects of his life, like the process that he went through to improve his knowledge, some religious and local values that he emphasized in his interaction with others, his roles in the endeavors of Indonesian nation to liberate the country and the people from colonialism, and his dedication as an ulama and a bureaucrat. Contemporary and next Muslim generations in this country are expected to know some principles of life and dedication of the figure. They might face special challenges, though they are expected to understand and follow the main objectives of struggles of former Muslim scholars. They should make sincere ulama as good models in their lives. Main data is collected through interview, documents, and observation. Units of data are compared one another to put into description. Data description is based on a research finding explaining that there were always teachers on Islam among Muslim communities and they usually took care for the condition of their community members